Analisis Pragmatik Strategi Kesantunan dalam Komentar di Media Sosial - Sulistianah Sulistianah; Fitria Nurhasanah; Tatu Siti Rohbiah (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This study explores the politeness strategies used in netizens’ comments on the policy of disbursing regional ASN teacher allowances across three social media platforms: Facebook, TikTok, and Instagram. The research is grounded in the growing phenomenon of public opinion expression in digital spaces, which often reflects varying levels of language politeness. The purpose of this study is to identify the types of politeness strategies used, examine the differences between platforms, and uncover the influencing factors. Employing a descriptive qualitative approach, the study applies Brown and Levinson’s politeness theory. Data were collected from user comments on a speech by President Prabowo Subianto regarding ASN teacher allowance distribution. The findings indicate that negative politeness and impoliteness strategies dominate across all platforms, with varying patterns. Facebook and TikTok featured more direct and sarcastic comments, while Instagram tended to display more indirect and polite expressions. Influencing factors include platform characteristics, the content of the speech, and the personal experiences of users. These findings contribute to digital pragmatics studies and offer practical insights for promoting ethical communication on social media.